3d Evaluation of Soft Tissue Changes Following Class III Orthognathic Surgery#x2013; A Systematic Review (Global Journal of Medical Research, 2020)
Background: The principle goal of orthognathic surgery is to establish a balanced and stable dento-skeleto facial complex.This mandates the surgeon and the orthodontist to be able to predict the soft tissue changes to the orthognathic surgery precisely, which is accurately possible using 3-D imaging. Aims: To evaluate the soft tissue changes following class III orthognathic surgery using 3-D imaging. Settings and Design:Systematic review. Methods and Material: This review was conducted according to Preferred Reporting Items for Systematic Reviews and meta-Analyses guidelines systematically searching the six databases including PubMed, Cochrane, Google Scholar, LILACS, Directory of Open Access Journals, and OpenGrey. Statistical analysis used: Not applicable. Results: This systematic review comprises of most UpToDate evidence from eleven articles answering the review questions. Conclusion: Le Fort I advancement shows significant increase in the alar width, alar cinch, upper lip, chelion, labiale superius, crista philtri,pronasale and subnasale. Mandibular setback shows significant backward movement of soft tissue point B, labialeinferius and subnasale and chin.
Keywords: 3-dimensional; class iii skeletal base; soft tissue; orthognathic; systematic review